Spontaneous utero-rectal fistula formation following reconstructive genital tract surgery: An interesting case report (Indian Journal of Case Reports, 2019)
A genital fistula is an abnormal communication between uterus with either urinary tract or gastrointestinal tract. Although genitourinary fistula is a common entity, rectovaginal or even uterorectal fistula is relatively uncommon. The etiology of fistula is usually due to an obstetric cause in a developing country, whereas, it is gynecological in the developing country. Whether etiology is obstetrical or gynecological, this develops following days of the procedure. Here, we present the case of a 17-year-old girl, who underwent vaginoplasty for cervical atresia and develop uterorectal fistula one and a half year following the first surgery. She was finally managed with hysterectomy.